Análisis del índice de morosidad del microcrédito en la Cooperativa de Ahorro y Crédito Ambato LTDA agencia Latacunga y su impacto en los resultados financieros del año 2022. - Manzano Toaquiza, Edgar Willian (2023)
Credit Unions play a fundamental role in the economic and social development of Ecuador in the field of financial intermediation. However, being involved in these activities exposes them to various risks that can affect their stability and sustainability in the market. It is necessary to investigate the delinquency rate and its impact on the financial results of the Cooperativa de Ahorro y Crédito Ambato Ltda., Latacunga agency in the period 2022. Which it was necessary to set an objective that guided the research to analyze the delinquency rate of the microcredit portfolio in order to assess the credit risk. The integrative project was oriented under a quantitative approach because numerical data provided by the institution was obtained through field research, bibliographic, and documentary that allowed to obtain first source data of descriptive and exploratory character. The population consisted of 7 managers of the financial institution, to whom the interview was applied in order to analyze delinquency, these being the instruments used to collect the information. The results obtained show that the delinquency rate of the microcredit segment varied from month to month, showing an annual percentage of 5.98%, which according to the Superintendence of Popular and Solidarity Economy is within the acceptable level. In addition, the causes of this were determined as the reduction of income by COVID-19, over-indebtedness, business bankruptcy, changes in the market, competition, lack of financial education, lack of counseling or internal problems such as inadequate placement, which allowed establishing an integrated proposal for strategies to strengthen the process of collection and recovery of the portfolio allowing to reduce delinquency and credit risk, accurate for making the right decisions and the optimized use of resources, culminating in economic growth for the financial institution.